Developing Character-Based Animated Learning Media Using Animaker: A Case Study in Indonesian Junior High School Social Studies - Afif Primahadi; Atik Purwasih (Digital Learning, Social Science, and Life-course Studies, 2025)
This study aims to develop and evaluate character-based learning media using the Animaker application for grade VII students at Junior High School (SMP) of Natar. The development of engaging and effective learning media is essential for improving student engagement and understanding, particularly in subjects like social studies, where complex concepts such as Social Interaction can be difficult for students to grasp. The study employed a Research and Development (R&D) approach, following the ADDIE model, which consists of five stages: research and data collection, product design, product development, product trials, and product revisions. The product developed is an animated video that integrates Social Interaction material with Islamic values, intended to support social studies education. The study’s evaluation process involved expert validation of the learning media and material. The media validation received a score of 90%, and the material validation achieved a perfect score of 100%, both categorized as "Very Strong." In addition, a student trial was conducted with 31 grade VII students, who showed positive responses and high engagement with the learning media. The effectiveness of the media was further confirmed through pre- and post-test assessments, demonstrating improved student understanding of the material. The results indicate that the Animaker-based learning media is valid, practical, and effective for enhancing student engagement and comprehension of social studies topics. This study contributes to the development of innovative educational tools that integrate multimedia to support active learning in the classroom.